The role of radiotherapy in localised and locally advanced prostate cancer - Michel Bolla; Ann Henry; Malcom Mason; Thomas Wiegel (Asian Journal of Urology)
For a patient suffering from non-metastatic prostate cancer, the individualized recommendation of radiotherapy has to be the fruit of a multidisciplinary approach in the context of a Tumor Board, to be explained carefully to the patient to obtain his informed consent. External beam radiotherapy is now delivered by intensity modulated radiotherapy, considered as the gold standard. From a radiotherapy perspective, low-risk localized prostate cancer is treated by image guided intensity modulated radiotherapy, or brachytherapy if patients meet the required eligibility criteria. Intermediate-risk patients may benefit from intensity modulated radiotherapy combined with 4–6 months of androgen deprivation therapy; intensity modulated radiotherapy alone or combined with brachytherapy can be offered to patients unsuitable for androgen deprivation therapy due to co-morbidities or unwilling to accept it to preserve their sexual health. High-risk prostate cancer, i.e. high-risk localized and locally advanced prostate cancer, requires intensity modulated radiotherapy with long-term (≥2 years) androgen deprivation therapy with luteinizing hormone releasing hormone agonists. Post-operative irradiation, either immediate or early deferred, is proposed to patients classified as pT3pN0, based on surgical margins, prostate-specific antigen values and quality of life. Whatever the techniques and their degree of sophistication, quality assurance plays a major role in the management of radiotherapy, requiring the involvement of physicians, physicists, dosimetrists, radiation technologists and computer scientists. The patients must be informed about the potential morbidity of radiotherapy and androgen deprivation therapy and followed regularly during and after treatment for tertiary prevention and evaluation. A close cooperation is needed with general practitioners and specialists to prevent and mitigate side effects and maintain quality of life. Keywords: Localized prostate cancer, Locally advanced prostate cancer, Brachytherapy, Intensity modulated radiotherapy, Short-term and long-term androgen deprivation therapy